2011
DOI: 10.1063/1.3665955
|View full text |Cite
|
Sign up to set email alerts
|

Highly unidirectional Y-junction-coupled S-section quantum-dot ring lasers

Abstract: Fabrication and characterization of Y-junction-coupled S-section InAs/InGaAs/GaAs quantum-dot ring lasers with high unidirectionality is reported. Stable unidirectional operation of the ring lasers is ensured by a new design that suppresses the unwanted counterpropagating modes more effectively than it was possible in the previous S-section-racetrack design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Control of the lasing direction was accomplished either with external optical injection 14) or special designs using selective electrical pumping. 15) Most recently a square ring=FP composite cavity laser, where deeply etched total internal reflector mirrors and a multimode interference (MMI) coupler were used to form a ring cavity and couple it with the FP cavity, was reported, 16) but the fabrication process was complex.…”
mentioning
confidence: 99%
“…Control of the lasing direction was accomplished either with external optical injection 14) or special designs using selective electrical pumping. 15) Most recently a square ring=FP composite cavity laser, where deeply etched total internal reflector mirrors and a multimode interference (MMI) coupler were used to form a ring cavity and couple it with the FP cavity, was reported, 16) but the fabrication process was complex.…”
mentioning
confidence: 99%
“…Another interesting line of research is found in refs. [24], [25] and [28] and involves the so-called S-ring laser, in which a cross-over waveguide connects two opposite sides of the ring, guiding light from one sense of rotation into the other, but not the other way around. Under lasing conditions, this topology favors directional operation, where the ratio of clockwise (CW) to counter clockwise (CCW) output power is observed as large as 13 dB in Hohimer et al [24], 25 dB in Cao et al [25] and 30 dB in Withers et al [28].…”
Section: Proposed Solutions To Reduce Feedback Sensitivitymentioning
confidence: 99%
“…[24], [25] and [28] and involves the so-called S-ring laser, in which a cross-over waveguide connects two opposite sides of the ring, guiding light from one sense of rotation into the other, but not the other way around. Under lasing conditions, this topology favors directional operation, where the ratio of clockwise (CW) to counter clockwise (CCW) output power is observed as large as 13 dB in Hohimer et al [24], 25 dB in Cao et al [25] and 30 dB in Withers et al [28]. The S-shaped micro laser idea was revived in Ren et al [38], where two of these lasers are coupled and operated under PT-symmetric conditions so as to achieve unidirectional single-mode operation.…”
Section: Proposed Solutions To Reduce Feedback Sensitivitymentioning
confidence: 99%
“…Hence, low-cost devices with simple fabrication processes are still required. Semiconductor ring lasers require relatively simple fabrication processes [19][20][21][22][23] compared with the grating-incorporated lasers. Devices having various configurations were studied to control the lasing of one of the two counter propagating modes 21) as well as the enhancement of light out coupling from the ring cavity.…”
mentioning
confidence: 99%
“…Semiconductor ring lasers require relatively simple fabrication processes [19][20][21][22][23] compared with the grating-incorporated lasers. Devices having various configurations were studied to control the lasing of one of the two counter propagating modes 21) as well as the enhancement of light out coupling from the ring cavity. 22) We recently reported the experimental demonstration of the stable single-mode operation of a circular ring=FP (RFP) composite cavity laser.…”
mentioning
confidence: 99%